Contact-Induced Grammaticalization Between Arabic Dialects - Leddy-Cecere, Thomas (My University, 2020)
This chapter describes the phenomenon of contact-induced grammaticalization\linebreak between Arabic dialects and its significance in accounting for the development of future tense markers across modern Arabic varieties. After an introduction to theoretical aspects of general grammaticalization theory and contact-induced grammaticalization in particular, discussion shifts to the identification of specific con\-tact-induced grammaticalization processes leading to the modern distribution of future tense-marking forms across the Arabic-speaking world. Finally, the significance of these findings to broader inquiry in Arabic dialectology and theoretical contact linguistics is considered.
Keywords: grammaticalization; Arabic dialects; tense markers